(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article explores the process of migration and colonization of the Lacandona Jungle through the novel hacia el confin, novela de la selva of Jesús Morales Bermúdez, and also from “El sueño de Carlos Hernández” chapter of the book Una tierra para sembrar sueños. Historia reciente de la Selva Lacandona, 1500-200, de Jan de Vos. It analyzes the discursive construction, in narrative terms, of the historical process from its representation as epic.